A methodological approach for assessing the effects of disturbance factors on the conservation status of Mediterranean coastal dune systems. Issue 2 (24th September 2012) - Attorre, Fabio; Maggini, Alberto; Di Traglia, Mario; De Sanctis, Michele; Vitale, Marcello
Abstract: Questions: How can the conservation status of Mediterranean coastal dunes be assessed? What is the effect of disturbance factors on it? Location: Tyrrhenian coast of Central Italy. Methods: Vegetation relevés along 164 transects lying perpendicular to the shoreline along the Tyrrhenian coast of Central Italy were used to identify the presence of dune habitats by means of TWINSPAN classification and detrended correspondence analysis. Multiple correspondence analysis was used to analyse relationship between habitats and disturbance factors. The resulting Burt's table was used to build an index (habitat‐disturbance, HDi) for analysing this relationship. Based on HDi values, a correspondence analysis (CA) between presence/absence of habitats and disturbances was performed. The overall plant species diversity of dunes was measured with NHDUNE, a modified version of the Shannon index. Multi‐way ANOVA procedure was used to investigate effect of single disturbance factors and their interactive effect on NHDUNE . Results: Classification and ordination procedures identified four sequential habitats moving from the shoreline to inland: annual vegetation on drift lines characterized by Cakile maritima ; embryonic shifting dunes dominated by Elymus farctus ; shifting dunes with Ammophila arenaria subsp. australis ; back dune grasslands characterized by Ononis variegata . CA showed that disturbance factors influence dune habitats differently. In particular, the Cakile community had a negative relationship with beach tourism and mechanical cleaning; the Elymus community had a positive relationship with beach tourism and mechanical cleaning and a negative relationship with erosion and bathing establishments; the Ammophila community had a negative relationship with mechanical cleaning and bathing establishments and a positive relationship with dune cross‐trampling; and the Ononis community had a negative relationship with bathing establishment. According to multi‐way ANOVA, single disturbance factors can have different effects on plant species diversity as measured by NHDUNE . However, the overall effect is negative, with erosion as a single factor and the combination of mechanical cleaning and bathing establishments significantly lowering the plant diversity of coastal dune systems. Conclusions: The proposed method allows a fast and replicable evaluation of the effects of disturbance factors on the conservation status of Mediterranean coastal dunes, providing the information necessary for development of conservation strategies focusing on a single habitat or on the overall dune system. Abstract : Mediterranean coastal dunes are threatened by human disturbances. For this reason the need for quantitatively assessing their conservation status and the effects of disturbance factors on them emerged. Our paper was aimed at evaluating the relationship between the presence of typical dune habitats and plant diversity indexes, and disturbance factors by means of Multiple Correspondence Analysis and multi‐way ANOVA.